The influence of fear of missing out, social media addiction, and boredom proneness on phubbing behaviour among young adults in Malaysia - Cheong, Jing Yan; Chong, Sze Foong; Hu, Langmingyue (2024)
Phubbing behaviour has become increasingly prevalent throughout the years with the significant increase of smartphone users. The present study examined the relationship between fear of missing out (FoMO), social media addiction (SMA), boredom proneness and phubbing among young adults in Malaysia. A quantitative research design was used with 66 young adults aged 18 and 25 from Malaysia. The participants completed an online survey that consisted of the Fear of Missing Out Scale, Bergen Social Media Addiction Scale, Shortened Boredom Proneness Scale and Phubbing Scale. Correlation analysis showed that FoMO, SMA, and boredom proneness have a positive relationship with phubbing behaviour among young adults in Malaysia. Multiple Linear Regression analysis showed SMA is the stronger predictor against phubbing behaviour, in comparison to the other two variables. This study can serve as a reference for future research on similar topics, as well as contribute to developing interventions to overcome this phubbing behaviour in young adults.